History of wolves [large type] : a novel - Fridlund, Emily (Center Point Large Print, 2017)
"Fourteen-year-old Linda lives with her parents in a nearly abandoned commune in the northern Minnesota woods. As she struggles to find a way out of the sequestered world into which she was born, Linda confronts the life-and-death consequences of the things people do--and fail to do--for the people they love"--